Medicine does not have to cure the poor”. The thought of Giovanni Bianchi (1693-1775) - Licata, Marta; Armocida, Giuseppe; Ciliberti, Rosagemma (Acta Biomedica Atenei Parmensis, 2019)
Letter To Editor